2020
DOI: 10.1016/j.socscimed.2020.113477
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in social institutions, perceived vulnerability and the adoption of recommended protective behaviors in Brazil during the COVID-19 pandemic

Abstract: The current worldwide COVID19 pandemic has required the rapid and drastic adoption of social distancing and protective measures as the leading method for reducing the spread of the disease and death. The purpose of this study is to investigate the factors associated with the adoption of such measures in a large sample of the Brazilian population. We relied on recreancy theory, which argues that confidence in the ability of social institutions and perceived vulnerability to the disease are central factors predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 44 publications
3
72
2
1
Order By: Relevance
“…The profile characterized as having general low levels of trust also was the least likely to comply with COVID-19 guidelines in this study. Hence, consistent with past research [ 39 , 40 ], our findings point to a potential risk for non-compliance with current guidelines associated with low levels of trust. The present findings may also explain some of the reports concerning younger people’s disregard to COVID-19 physical distancing guidelines [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…The profile characterized as having general low levels of trust also was the least likely to comply with COVID-19 guidelines in this study. Hence, consistent with past research [ 39 , 40 ], our findings point to a potential risk for non-compliance with current guidelines associated with low levels of trust. The present findings may also explain some of the reports concerning younger people’s disregard to COVID-19 physical distancing guidelines [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Like China and Italy, the nationwide smart lockdown was imposed on 27 th March 2020 that later ended in different phases [6]. The aim of restricting activities was to save lives by preventing viral transmission, to reduce its incidence, and to decrease the burden on the medical care system [7]. School closure due to pandemics like flu or severe acute respiratory syndrome (SARS), had remained a successful attempt to reduce the transmission rate of viruses and to flatten the peak of the incidence of disease [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…School closure due to pandemics like flu or severe acute respiratory syndrome (SARS), had remained a successful attempt to reduce the transmission rate of viruses and to flatten the peak of the incidence of disease [8,9,10]. This strategy appeared to be very effective in the way that it reduced the contact between the students and protected them from getting infections [11], but other hand it afflicted the daily routine of the students and everyone else [7].…”
Section: Introductionmentioning
confidence: 99%
“…36 Cognitive behavior is a major focus of the previous literature on the adoption of preventive health behaviors. For example, Storopoli et al 37 applied recreancy theory in a Brazil study of factors associated with the adoption of preventive behavior to cope with the pandemic crisis. They reported that the effect of perceived vulnerability depends on confidence in oneself and confidence in social institutions (ie, government, hospitals, the media, etc.…”
mentioning
confidence: 99%